Blue, green, and orange-red emission from Polystyrene microbeads for solid-state white-light and multicolor emission - Sonawane, Swapnil L.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Solid-state white-light emission was achieved from polystyrene (PS) microbeads incorporated with fluorophores based on perylene bisimide (PBITEG) and oligo(p-phenylenevinylene) (OPV) as acrylic cross-linkers. The PS beads incorporated with only PBITEG gave intense orange-red emission; PS incorporated with OPV exhibited blue-emission, whereas a series of polymers incorporating both cross-linkers exhibited varying shades of white-light emission. One of the PS samples, PS-PBITEG-6.25-OPV-4.28 (PBITEG incorporation: 6.25 X 10(-7) mole; OPV incorporation: 4.28 x 10(-7) mol), exhibited pure white-light emission in the powder form with CIE coordinates (0.33, 0.32). The rigid aromatic cross-linkers were incorporated into the PS backbone in a two-stage dispersion polymerization to afford PS beads in the size range 2 to 3 mu m. The incorporation of fluorophores as cross-linkers enabled covalent attachment of the dye to the polymer backbone, avoiding dye leakage besides avoiding aggregation-induced fluorescence quenching.